Iran health insurance system in transition: equity concerns and steps to achieve universal health coverage - Doshmangir, Leila (Int J Equity Health, 2021)
BACKGROUND: Equity, efficiency, sustainability, acceptability to clients and providers, and quality are the cornerstones of universal health coverage (UHC). No country has a single way to achieve efficient UHC. In this study, we documented the Iranian health insurance reforms, focusing on how and why certain policies were introduced and implemented, and which challenges remain to keep a sustainable UHC. METHODS: This retrospective policy analysis used three sources of data: a comprehensive and chronological scoping review of literature, interviews with Iran health insurance policy actors and stakeholders, and a review of published and unpublished official documents and local media. All data were analysed using thematic content analysis. RESULTS: Health insurance reforms, especially health transformation plan (HTP) in 2014, helped to progress towards UHC and health equity by expanding population coverage, a benefits package, and enhancing financial protection. However, several challenges can jeopardize sustaining this progress. There is a lack of suitable mechanisms to collect contributions from those without a regular income. The compulsory health insurance coverage law is not implemented in full. A substantial gap between private and public medical tariffs leads to high out-of-pocket health expenditure. Moreover, controlling the total health care expenditures is not the main priority to make keeping UHC more sustainable. CONCLUSION: To achieve UHC in Iran, the Ministry of Health and Medical Education and health insurance schemes should devise and follow the policies to control health care expenditures. Working mechanisms should be implemented to extend free health insurance coverage for those in need. More studies are needed to evaluate the impact of health insurance reforms in terms of health equity, sustainability, coverage, and access.